Analysis of Customer Satisfaction and Loyalty Through the Tiktok Application in the Groceries Department of Hypermart Pakuwon Mall Yogyakarta - RA. Kooswinarning Definta Indraswari; Binarin Tirto Andika (Publikasi Indonesia, 2026)
This research examines customer satisfaction and loyalty through TikTok promotion in the groceries department of Hypermart Pakuwon Mall Yogyakarta. The study focuses on key variables, including TikTok promotion, customer loyalty, word of mouth, and price fairness. Data were collected through a structured questionnaire distributed to 320 Hypermart customers who actively shop at the Pakuwon Mall Yogyakarta outlet. A descriptive analysis approach was employed by calculating average scores and comparing them with predefined assessment standards to evaluate customer perceptions. The findings indicate that TikTok promotion is perceived as effective in increasing customer interest, influencing purchasing decisions, and building positive perceptions of product value. Customer loyalty is categorized as high, as reflected in customers’ willingness to revisit the store and recommend Hypermart to others. Word of mouth also shows a high level, particularly in customers’ preference for choosing Hypermart over competing retailers, although customers’ willingness to actively share product content on social media remains moderate. Furthermore, price fairness is perceived positively, with customers considering Hypermart’s product prices to be fair, reasonable, and affordable. Overall, the results suggest that TikTok promotion contributes positively to strengthening customer loyalty, encouraging favorable word of mouth, and reinforcing perceptions of price fairness. These findings highlight the importance of optimizing digital marketing strategies, especially social media–based promotion, to enhance customer engagement, competitiveness, and long-term loyalty in the retail sector.